Information Technology Units in Bachelor Degree of Library and Information Science (LIS) Curriculum in Indonesia / Nove E. Variant Anna - Variant Anna, Nove E. (2011)
The aim of this paper to discovers and describes the type of information technology (IT) units in bachelor degree of LIS education curriculum through its university‘s official websites. This paper tries to find out what are the types of IT units in bachelor degree of LIS course in Indonesia? How does it fit the need of the information age? The research method is using curriculum observation through the university‘s official websites. The author search for IT units based on its name, cluster that available on the curriculum structure, and interviews some lecturers on the university regarding of the curriculum structure. Following that, the data is classified into some categories and finally each category is discussed. The research finding from 8 universities conduct LIS education was surveyed shows different portion of IT units. The range of the IT units offered in the curriculum is from 6 to 14 units. This is because each university has specialty that differ from one to another. However, those IT unit titles have similarity such as introduction to basic computer and information technology, information retrieval system, library automation, and digital library and web design. All of the IT units aim to support student skill on IT so they can help them handle the library and information job. This is only preliminary research, and there were still many areas that need to be covered. For further research, the involvement of the LIS course coordinator and IT lecturer need to discover and to gain in-depth information about the role of IT units in LIS education.